THE MAIN EFFECTS OF GENDER AND AGE OF FACEBOOK USERS ON MULTIPLE FACETS OF FACEBOOK INTENSITY - พัฒน์ธนญานนท์, พีรยุทธ์ (RMUTT Global Business and Economics Review, 2016)
This research aims to investigate if there were differences between Facebook users in different gender and age groups on a linear combination of the multiple facets of Facebook intensity which include persistence to use, boredom, overuse and self-expression. A sample of 400 Facebook users was drawn by a multistage sampling method; respondents are made up of men and women, aged 13 years or older, and lived in Thailand. The respondents were asked to fill up an online rating scale survey. A multivariate analysis of variance was conducted to assess statistical significance. Differences were found in all four multiple facets of Facebook intensity among Facebook users of different gender and age groups. Practical implications for marketing professionals were suggested. Future researchers might examine different variables.